Nursing Education for Pediatric Cardiac Care Centers in Developing Countries - Peterson, Jennifer (Journal of Humanitarian Cardiovascular Medicine, 2023)
Summary Pediatric cardiac programs achieve excellent patient outcomes through the teamwork of a highly capable interdisciplinary team. Nurses are key members of this team, and must possess and highly specialized set of skills and knowledge. A comprehensive nursing education program is needed to develop the necessary skills and knowledge to care for critically ill infants and children with heart disease who are often highly unstable, complex, and vulnerable. Orientation of novice nurses or those who are new to the unit begins with a needs assessment, resulting in a comprehensive plan to achieve required competencies. Nurse residency programs are one method to provide a comprehensive orientation to novice nurses, using a combination of didactic instruction, preceptored clinical experiences, and simulation. An ongoing nursing education plan is also important to refresh skills, especially with high-risk, low-volume procedures, as well as to meet regulatory requirements and develop new skills and knowledge. A key component of the pediatric cardiac nursing education plan is development of preceptors, who provide hands-on instruction to mentor new nurses to develop the needed skills and knowledge, while ensuring that patients receive safe care. Preceptor development can also provide experienced bedside nurses with opportunities to develop their own knowledge and to continue professional development, which helps to positively influence job satisfaction. Numerous resources are available to develop a curriculum or the pediatric cardiac program. Evaluation is also an important component of the nursing education program, to quantify individual as well as programmatic outcomes.